The Effect of Gorilla Marketing on the Brand Reputation of Smartphone Companies (A Survey Study on Samsung Customers in the Syrian Coast) - قاسم سامر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to determine the effect of gorilla marketing with its applications (creativity, simplicity and clarity, and surprise) on the brand reputation of smart phone companies in the Syrian coast. The study relied on the deductive approach in thinking, and relied on the descriptive approach to describe and analyze the research variables based on the primary data that was collected, as a survey was conducted on smart phone users on the Syrian coast to collect the necessary primary data, and the variables were measured on all the primary data that were collected. It was collected through a questionnaire that was designed by looking at previous studies and literature, and in order to test hypotheses, the raw data was dumped into a database that was analyzed using SPSS version /20/. The study concluded that gorilla marketing has an impact on the reputation of the brand of smart phone companies through its applications of creativity, simplicity and clarity in presenting its products to customers, and the company’s advertisements are innovative, interesting, different and distinctive from others, and are considered new for the customer.